Long-peptide vaccination with driver gene mutations in p53 and Kras induces cancer mutation-specific effector as well as regulatory T cell responses. (2nd December 2018) - Quandt, Jasmin; Schlude, Christoph; Bartoschek, Michael; Will, Rainer; Cid-Arregui, Angel; Schölch, Sebastian; Reissfelder, Christoph; Weitz, Jürgen; Schneider, Martin; Wiemann, Stefan; Momburg, Frank; Beckhove, Philipp
ABSTRACT: Mutated proteins arising from somatic mutations in tumors are promising targets for cancer immunotherapy. They represent true tumor-specific antigens (TSAs) as they are exclusively expressed in tumors, reduce the risk of autoimmunity and are more likely to overcome tolerance compared to wild-type (wt) sequences. Hence, we designed a panel of long peptides (LPs, 28–35 aa) comprising driver gene mutations in TP35 and KRAS frequently found in gastrointestinal tumors to test their combined immunotherapeutic potential. We found increased numbers of T cells responsive against respective mutated and wt peptides in colorectal cancer patients that carry the tested mutations in their tumors than patients with other mutations. Further, active immunization of HLA(-A2/DR1)-humanized mice with mixes of the same mutated LPs yielded simultaneous, polyvalent CD8 + /CD4 + T cell responses against the majority of peptides. Peptide-specific T cells possessed a multifunctional cytokine profile with CD4 + T cells showing a TH 1-like phenotype. Two mutated peptides (Kras[G12V], p53[R248W]) induced significantly higher T cell responses than corresponding wt sequences and comprised HLA-A2/DR1-restricted mutated epitopes. However, vaccination with the same highly immunogenic LPs strongly increased systemic regulatory T cells (Treg ) numbers in a syngeneic sarcoma model over-expressing these mutated protein variants and resulted in accelerated tumor outgrowth. In contrast, tumor outgrowth was delayed when vaccination was directed against tumor-intrinsic Kras / Tp53 mutations of lower immunogenicity. Conclusively, we show that LP vaccination targeting multiple mutated TSAs elicits polyvalent, multifunctional, and mutation-specific effector T cells capable of targeting tumors. However, the success of this therapeutic approach can be hampered by vaccination-induced, TSA-specific Treg s.